Preparation of Cationic Lipid-coated Ultrasound Contrast Agents and Noninvasive Gene Transfection Via Ultrasound-targeted Microbubble Destruction - Yang, Feng; Li, Yue; Liufu, Chun; Wang, Yi; Chen, ZhiYi (Current Pharmaceutical Design, 2018)
Purpose: Ultrasound contrast agents involving a therapeutic drug applied during enhanced imaging can be used for targeted therapy. The preparation of contrast agents is a precondition and basis for the use of multifunctional contrast agents in molecular imaging. Methods: This study uses thin-film hydration-mechanical vibration to carry out the preliminary preparation of a cationic contrast agent (CCA); characterizes the particle diameter, potential, distribution, and concentration of the agents; and optimizes the factors affecting the preparation of the agents. Results: This study found that thin-film hydration-mechanical vibration methods offer a better preparation effectiveness and achieve smaller particle diameters and more even distributions, as well as give better imaging performance. Different concentrations of CCA and plasmid and different gene transfection methods can produce different degrees of sonoporation to achieve optimal transfection efficiency. Ultrasound parameters have a great influence on transfection efficiency and plasmid integrity. A previous study confirmed that the ultrasound parameters of 1 MHz, 1 W/cm2, a duty cycle controller (DC) of 20%, and irradiation for 1 min can well deliver genes to tumor cells, with little impact on cell survival. Conclusion: Our findings indicate that ultrasound-targeted microbubble destruction (UTMD)-mediated CCA destruction facilitates gene transfection and may represent an effective gene delivery method for cervical cancer therapy.
Keywords: cationic